2016
DOI: 10.1371/journal.pone.0167005
|View full text |Cite
|
Sign up to set email alerts
|

Selection Signatures in Four Lignin Genes from Switchgrass Populations Divergently Selected for In Vitro Dry Matter Digestibility

Abstract: Switchgrass is undergoing development as a dedicated cellulosic bioenergy crop. Fermentation of lignocellulosic biomass to ethanol in a bioenergy system or to volatile fatty acids in a livestock production system is strongly and negatively influenced by lignification of cell walls. This study detects specific loci that exhibit selection signatures across switchgrass breeding populations that differ in in vitro dry matter digestibility (IVDMD), ethanol yield, and lignin concentration. Allele frequency changes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 66 publications
0
3
0
Order By: Relevance
“…The findings of the study suggested that the extent of substitution of the xylan backbone of hemicellulosic polysaccharides by arabinose (DHS), the degree of xylan acetylation (DHA) and feruloyation (DHF), and the ratio of para-coumaric acid to acid detergent lignin (pCA/ADL) were important areas that can be exploited to obtain greater quality of substrate for bioethanol production. Similarly, Chen et al (2016) also detected specific loci for different switchgrass populations, for in vitro dry matter digestibility and ethanol yield. The study successfully discovered potential markers that can be utilised for breeding switchgrass varieties that can yield higher ethanol titres.…”
Section: Improvements In Bioenergy Crops Through Breeding Marker-assmentioning
confidence: 85%
“…The findings of the study suggested that the extent of substitution of the xylan backbone of hemicellulosic polysaccharides by arabinose (DHS), the degree of xylan acetylation (DHA) and feruloyation (DHF), and the ratio of para-coumaric acid to acid detergent lignin (pCA/ADL) were important areas that can be exploited to obtain greater quality of substrate for bioethanol production. Similarly, Chen et al (2016) also detected specific loci for different switchgrass populations, for in vitro dry matter digestibility and ethanol yield. The study successfully discovered potential markers that can be utilised for breeding switchgrass varieties that can yield higher ethanol titres.…”
Section: Improvements In Bioenergy Crops Through Breeding Marker-assmentioning
confidence: 85%
“…Conventional breeding techniques advance our understanding toward marker-assisted selection for biomass-related traits, stress tolerance, and scarification in biofuel grasses and woody plants. In switchgrass, marker-assisted breeding enabled the understanding of substitution of cell wall hemicellulose polymers backbone and remodeling ( De Souza et al, 2015 ) whereas identification of specific loci was identified from potential markers for high ethanol generation from switchgrass populations ( Chen et al, 2016 ). Prairie cordgrass is a potential C 4 bioenergy crop, and two clones of prairie cordgrass were crossed and developed SSR markers for marker-assisted selection of biomass traits ( Gedye et al, 2012 ).…”
Section: Tools and Strategies To Enhance Biomassmentioning
confidence: 99%
“…The genotypic effects for ADF, IVDT, NDFD, and starch content were significant, so it should be possible to improve the DE content of barleybased forage feedstuff. Work in other species, such as that of Vogel (2013) and Chen, Kaeppler, Vogel, and Cassler (2016) in switchgrass (Panicum virgatum L.) and Li et al (2011) in alfalfa (Medicago sativa L.), has shown that it is possible to identify both high FAs and improved nutritive value traits. In their review, Capstaff and Miller (2018) noted that the greatest concurrent improvements in FA and nutritional content of forage crops had occurred in Medicago spp., Trifolium spp., Lolium, and Festuca.…”
Section: Improving the Forage Accumulation-nutritive Value Relationshipmentioning
confidence: 99%